O Princípio da PAR CONDITIO CREDITORUM - Camargo, Camila Ramos de (2022)
This dissertation intends to go deeper into the principle of par conditio creditorum and its exceptions through a detailed analysis of the understanding of the Portugues courts' jurisprudence. It aims to understand which differentiations are justified for objective reasons, according to the rules of CIRE´s Article 194. The thematic is a pragmatic matter due to the conflicting and divergent positions in jurisprudence. Occasionally, contrary to the par conditio creditorum principle in resulting in an express violation of this principle. Thus, although the object of the dissertation allows us to make a merely practical approach, a theoretical study will be necessary to serve as a basis for better understanding. In order to achieve the goal of the dissertation a multi-stage analysis is required. First of all, to analyze the general framework of the Special Process of Revitalization, to proceed the complete understanding of the historical evolution, concept and main characteristics, viability for the recovery. Further, to analyze the requirements for the presentation of this process. Next, will proceed to the complex analysis about the handling and processing of the PER, especially the advantages and disadvantages of this process for the debtor. In the third phase, it will be studied the guiding principles of credit protection.It is important to examine: the principle of priority (Prior In Tempore Potior in Iure) and the Principle of Equality (Par Conditio Creditorum). At the final phase of the dissertation, it moves on to the goal of the discussion which, through the analysis and reflection of jurisprudence. The thesis end up presenting the position of the Portuguese Court on the abstract definition of differentiations justified by objective reasons, namely in relation to the consent of the affected creditor, financing, essential votes for the approval of the plan, classification of credits and hierarchical grade.